2016
DOI: 10.1007/s12035-016-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Long Non-Coding RNAs Were Predicted to Be Involved in the Control of Signaling Pathways in Pediatric Astrocytoma

Abstract: Expression changes for long non-coding RNAs (lncRNAs) have been identified in adult glioblastoma multiforme (GBM) and in a mixture of adult and pediatric astrocytoma. Since adult and pediatric astrocytomas are molecularly different, the mixture of both could mask specific features in each. We determined the global expression patterns of lncRNAs and messenger RNA (mRNAs) in pediatric astrocytoma of different histological grades. Transcript expression changes were determined with an HTA 2.0 array. lncRNA interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…Accumulative evidence has indicated that lncRNAs are ectopically expressed and are widely involved in multiple biological processes of GBM . Long noncoding RNAs play crucial roles in proliferation and metastasis of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulative evidence has indicated that lncRNAs are ectopically expressed and are widely involved in multiple biological processes of GBM . Long noncoding RNAs play crucial roles in proliferation and metastasis of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of endogenous miRs that serve indispensable roles in the translation of the genetic code and expression of proteins. It has been previously reported that there is a correlation between HBV infection and certain miRs, and therefore this group of miRs should receive more attention due to their potential for acting as biomarkers for disease diagnosis (Rohan et al 2018, Burmi et al 2019, Ruiz Esparza-Garrido et al 2017. miR-122 is an miR abundant in the healthy liver, which plays a role in stimulating the translation of HBV and HCV RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs) represent a significant fraction of the human genome [1], and the great diversity and forms of action of these RNA species has put them at the center of biomedical research of diseases, such as cancer [2][3][4]. LncRNAs are not the exception, and many of them have been proposed as possible diagnostic and prognostic biomarkers for Ast [5]. LncRNAs are RNAs of more than >200 nucleotides in length, which have to meet certain additional criteria to be classified within this category [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many cellular processes are regulated by lncRNAs and this could be at both cytoplasmic and nuclear levels, as well as distance by moving them to their target tissues through different bodily fluids, such as blood [8]. LncRNAs exert their functions by establishing interactions with other lncRNA and RNA species, as well as with proteins [9], and changes on their functioning have been associated with cancer and particularly with astrocytomas (Ast) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation